Expression of the heparin-binding growth factors Midkine and Pleiotrophin during ocular development - Cui, Ruda (Gene Expr Patterns, 2019)
Midkine (MDK) and Pleiotrophin (PTN) belong to a group of heparin-binding growth factors that has been shown to have pleiotropic functions in various biological processes during development and disease. Development of the vertebrate eye is a multistep process that involves coordinated interactions between neuronal and non-neuronal cells, but very little is known about the potential function of MDK and PTN in these processes. In this study, we demonstrate by section in situ hybridization, the spatiotemporal expression of MDK and PTN during ocular development in chick and mouse. We show that MDK and PTN are expressed in dynamic patterns that overlap in a few non-neuronal tissues in the anterior eye and in neuronal cell layers of the posterior eye. We show that the expression patterns of MDK and PTN are only conserved in a few tissues in chick and mouse but they overlap with the expression of some of their receptors LRP1, RPTPZ, ALK, NOTCH2,ITGβ1, SDC1, and SDC3. The dynamic expression patterns of MDK, PTN and their receptors suggest that they function together during the multistep process of ocular development and they may play important roles in cell proliferation, adhesion, and migration of neuronal and non-neuronal cells.